Metode Memaksimalkan Peran Kelurahan Terhadap Pengelolaan Bank Sampah Melalui Program 3R (Reduce, Reuse Dan Recycle) Di Yogyakarta - Widyayanti, Evi Rosalina; Insiatiningsih (LP3M Universitas Putra Bangsa, 2022)
Low public awareness of waste needs to be the main concern for government officials from various levels of society. Because in the long term it will become a national problem that is very troublesome and has a negative impact if the solution is not immediately solved. Based on this, the PKM program is carried out to seek the right and maximum method that can be carried out by the Waste Bank which has been managed by all urban villages in the city of Yogyakarta so that it can continue to reduce waste that goes to the TPA through the Reduce, Reuse and Recycle program. In the PKM Program, the author collaborates with Panembahan Village as partner 1 and the Panembahan Garbage Bank Association, Yogyakarta City Palace district as partner 2 to jointly maximize the potential of waste banks in the region. This program lasts for 3 months with various theoretical and practical training programs whose benefits are directly felt by the community in Panembahan Village, Keraton District, Yogyakarta City. Activities carried out include program socialization, 3R (Reduce, Reuse and Recycle) training, workshops on utilizing waste for craft, financial management training resulting from waste management in waste banks by cultivating saving in waste banks, and others